Strategy for Increasing Consumer Satisfaction of Hospital Services Using Importance-Performance Analysis (IPA) Approach - Utami, Sri Pangesti; Maarif, M. Syamsul; Simanjuntak, Megawati (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
The Covid 19 Pandemic further sharpened hospital competition that required the improvement of customers satisfaction. The purpose of this study was to analyze the level of satisfaction, the difference in service satisfaction between BPJS and Non-BPJS patients, and to formulate a strategy to improve patient satisfaction. The research used quantitative descriptive using an online survey and Focus Group Discussion (FGD). The number of respondents was 764, including 248 BPJS and 516 Non-BPJS respondents. The variables used in this study consist of reliability, responsiveness, assurance, empathy, and physical evidence. Data analysis used Customer Satisfaction Index (CSI), independent t-test, and Importance-Performance Analysis (IPA). The Customer Satisfaction Index (CSI) is 80.39% (BPJS 80.35% and Non-BPJS 80.40%), meaning patient satisfaction toward UMMI Bogor Hospital belongs to satisfy. There was no significant difference in the level of satisfaction of Non-BPJS patients and BPJS patients. The attributes that belonged to the main priority in repairs is the waiting time of polyclinic services, the timely presence of doctors in polyclinics, the friendliness and decency of pharmacy officers, the comfort of the waiting room, the cleanliness of the waiting room, and the neatness of building facilities, the safety of the hospital environment, the availability of medical devices, and the ease of complaining. Keywords: customer satisfaction index, importance-performance analysis, non-BPJS, satisfaction, social security organizing agency (BPJS)